Modeling the Structural Relations among School Bonding, Identity Styles, and Family Climate with Mediation of Self-Compassion - A. R. Merati; E. Ghadampour, Ph.D.; H. Veiskarami, Ph.D. (خانواده و پژوهش, 2022)
This study examined the relationships among school bonding, identity styles, and family climate with mediation of self-compassion. This research had a descriptive-correlational design. The statistical population of the study comprised all senior high school students in Kangavar in 2020-21 school year from among whom 520 students were selected through multi-stage cluster sampling method. The research instruments included RezaeeSharif School Bonding Questionnaire (2014), Identity Style Inventory (Berzonsky, 1992), Heilbrun’s Parent-Child Interaction Rating Scale (1964), and Self-Compassion Scale (Neff, 2003). The proposed model was evaluated using SPSS and AMOS. Structural equation modeling was performed to examine the relations among the variables of the research.  The results demonstrated that identity styles and family climate had direct, positive effects on school bonding. Findings also indicated that identity styles and family climate could predict school bonding, while self-compassion mediated this association.  Accordingly, predictor variables can be considered as key components of students’ connection to their schools and parents and teachers training in this field can enhance school bonding.